The new challenges raised by investment arbitration for the EU legal order - Yves Mersch; Laurie Achtouk-Spivak; Georges Affaki; Cristina Contartese; Ramón Vidal Puig (European Central Bank (ECB), 2019)
The five contributions in this legal working paper discuss various aspects of investment arbitration. They were originally presented at the ECB legal colloquium on 'The new challenges raised by investment arbitration for the EU legal order' which took place in Frankfurt am Main in 2019.
Keywords: K; 330; European Central Bank; investment arbitration; bilateral investment treaties (BITs); dispute settlement mechanism; Achmea; Opinion 1/17; arbitration tribunals; division of competence; investor-state arbitration clauses; with investor-state dispute settlement mechanisms (ISDS); Court of Justice of the European Union (CJEU); Comprehensive Economic and Trade Agreement (CETA) tribunal